Turmeric in the management of oral submucous fibrosis – A systematic review and meta-analysis - Ingle, Ekta (International Journal of Health Sciences, 2020)
Introduction: Oral submucous fibrosis (OSMF), a premalignant condition, is frequently occur in the buccal mucosa and is associated with betel nut chewing. Various treatment modalities are tested to treat this condition. An effective intervention is needed, which is cost effective, safe, and efficient, considering the disease burden in high incident countries. Turmeric has promising results in the management of OSMF because of its potent anti-inflammatory and anti-oxidant pharmacological actions. Objectives: The objectives of the study were to analyze the efficacy of turmeric in managing OSMF based on the available literature. Methodology: The articles were searched from Medline/PubMed and Journal of web, which were published from 2000 to 2019 and reviewed for the determined outcomes. Results: The review showed a positive response for turmeric usage in managing OSMF, in terms of improved mouth opening and decreased burning sensation. Conclusion: Multicenter studies in high incidence countries with long-term follow-up are recommended to better understand the curative aspect of curcumin in OSMF.